The acute diuretic effect of an ethanolic fraction of Phyllanthus amarus (Euphorbiaceae) in rats involves prostaglandins - Alain N'guessan Yao; Mamadou Kamagaté; Augustin Kouao Amonkan; Philippe Chabert; Fidèle Kpahé; Camille Koffi; Mathieu N'goran Kouamé; Cyril Auger; Séraphin Kati-Coulibaly; Valérie Schini-Kerth; Henri Die-Kakou (BMC, 2018)
Abstract Background Phyllanthus amarus (Schum & Thonn), a plant belonging to the family of Euphorbiaceae is used in Ivorian traditional medicine to treat cardiovascular disorders such as hypertension. However, although this plant has been described as a diuretic agent, the underlying mechanism remains unclear. Therefore, the aim of the present study was to investigate the mechanism action of diuretic effects of an ethanolic fraction of Phyllanthus amarus (EFPA) in rats. Methods Effects of EFPA on urinary excretion were carried out for doses ranging from 5 to 80 mg/kg given by intraperitoneal injection (i.p.) and compared with that induced by furosemide (5 mg/kg) after 8 h. Thereafter, the diuretic activity of EFPA was also evaluated in the presence of indomethacin (5 mg/kg, i.p.) in order to determine the involvement of prostaglandins, after 24 h. Results Between 5 and 80 mg/kg, EFPA induced a significant urinary excretion. The profile of urinary excretion showed that after 2 h, the highest dose of 80 mg/kg induced a urinary volumetric excretion (UVE), which was similar to that induced by furosemide. After 24 h, EFPA at 10 mg/kg increased significantly UVE, Na+ (43 mEq) and Cl¯ (97 mEq) urinary excretions without promoting kaliuresis. In rats pretreated with indomethacin, the urinary excretion and the natriuretic response of EFPA were significantly reduced. Conclusion Altogether, this study has shown that EFPA promotes a significant urinary excretion of water and Na+, confirming its diuretic activity. Moreover, the increased diuresis could be attributed, at least in part, to the involvement of prostaglandins.